Two Sinorhizobium meliloti glutaredoxins regulate iron metabolism and symbiotic bacteroid differentiation. (14th August 2012) - Benyamina, Sofiane M.; Baldacci‐Cresp, Fabien; Couturier, Jérémy; Chibani, Kamel; Hopkins, Julie; Bekki, Abdelkader; de Lajudie, Philippe; Rouhier, Nicolas; Jacquot, Jean‐Pierre; Alloing, Geneviève; Puppo, Alain; Frendo, Pierre
Summary: Legumes interact symbiotically with bacteria of the Rhizobiaceae to form nitrogen‐fixing root nodules. We investigated the contribution of the three glutaredoxin (Grx)‐encoding genes present in the Sinorhizobium meliloti genome to this symbiosis. SmGRX1 (CGYC active site) and SmGRX3 (CPYG) recombinant proteins displayed deglutathionylation activit y in the 2‐hydroethyldisulfide assay, whereas SmGRX2 (CGFS) did not. Mutation of SmGRX3 did not affect S. meliloti growth or symbiotic capacities. In contrast, SmGRX1 and SmGRX2 mutations decreased the growth of free‐living bacteria and the nitrogen fixation capacity of bacteroids. Mutation of SmGRX1 led to nodule abortion and an absence of bacteroid differentiation, whereas SmGRX2 mutation decreased nodule development without modifying bacteroid development. The higher sensitivity of the Smgrx1 mutant strain as compared with wild‐type strain to oxidative stress was associated with larger amounts of glutathionylated proteins. The Smgrx2 mutant strain displayed significantly lower levels of activity than the wild type for two iron‐sulfur‐containing enzymes, aconitase and succinate dehydrogenase. This lower level of activity could be associated with deregulation of the transcriptional activity of the RirA iron regulator and higher intracellular iron content. Thus, two S. meliloti Grx proteins are essential for symbiotic nitrogen fixation, playing independent roles in bacterial differentiation and the regulation of iron metabolism.